MORTALITY PATTERN OF TURKEYS IN AN ORGANIZED POULTRY FARM - C. Pandian; A.V. Omprakash; R. Richard Churchil; M. Babu; D.Thyagarajan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was carried out in turkey birds maintained at Institute of Poultry Production and Management, TANUVAS, Chennai, spread over 3 years (2009-2010 to 2011-2012). Causative agents were listed and per cent mortality was calculated during different seasons. There are four seasons, viz. winter, summer, southwest monsoon and northeast monsoon. Brooder and grower turkey (0-20 weeks) and adult turkey (21-68 weeks) were reared in deep litter system of management. The overall mortality pattern during brooder and grower period (0-20 weeks) revealed that in southwest monsoon the mortality was the highest (53.81 %), followed by 22.39 % during summer, 17.93%  in northeast monsoon and the lowest (5.86%) in winter. The overall mortality due to omphalitis was high (28.71%) and significantly (P